Worldwide asbestos supply and consumption trends from 1900 through 2003 - Virta, Robert L. (Reston, VA, 2006)
"This Circular updates and supersedes U.S. Geological Survey (USGS) Open-File Report 03–083, "Worldwide Asbestos Supply and Consumption Trends from 1900 to 2000," with the addition of supply and consumption estimates and analysis from 2001 through 2003 and revisions to the consumption estimates for 1998 through 2000. The text from Open-File Report 03–083 also has been updated in this Circular to include revisions to and expansion of the time-series coverage. The use of asbestos is one of the most controversial issues surrounding the industrial minerals industry. Its carcinogenic nature, an overall lack of knowledge of minimum safe exposure levels, its widespread use for more than 100 years, and the long latency for the development of lung cancer and mesothelioma are the main contributing factors to these controversies. Another factor is that, despite decades of research, the mechanisms responsible for its carcinogenic properties are still largely unknown. The United States produced about 3.29 million metric tons (Mt) of asbestos and used approximately 31.5 Mt between 1900 and 2003. About half of this amount was used after 1960. In 2002, the last asbestos mine in the United States closed, marking the end of more than 110 years of U.S. asbestos production. Cumulative world production from 1900 through 2003 was about 181 Mt. If one assumes that unusually large stocks were not maintained and that world consumption roughly equaled production, then about half of the world production and consumption occurred between the end of 1976 and the end of 2003. [...]"